Heat treatment effects on the structural and optical properties of thin Bi2(Se1-xTex)3 films. Issue 21 (1st November 2022) - El-Qahtani, Z.M.H.; El-Hadek, Medhat A.; Alotaibi, Maged F.; Petkov, P.; Adam, A.M.
Abstract: Thin layers of Bi2 -chalcogenides, in the form of Bi2 (Se1-x Tex )3 films, were evaporated on glass substrates by means of the vacuum thermal evaporation. Microstructure of the as prepared layers was investigated by x-ray diffraction (XRD) analysis. Identifications of the surface morphology and roughness were determined via scanning electron microscope (SEM). Optical transmissivity spectra proved that the as prepared films have low transparency with growing trend upon increasing the wavelength beyond the infra-red region. Low transmittance was observed for the as prepared films. Heat treatment, in the form of temperature annealing, was carried out aiming at boosting the structural features and the materials transmissivity. Structural properties and surface features of the annealed films were probed also via XRD and SEM analyses. It was found that the crystal size increases while the micro-strain and the dislocation density decrease obviously due to annealing. It was also observed that the annealing process significantly enhances the materials transmission especially in the range of higher wavelengths. Optical band gap was studied after annealing at various temperatures. Notable change in the band gap value was observed as a result of annealing. The band gap of the undoped (Bi2 Se3 ) materials showed significant rise from 0.14 to 1.79 eV due to annealing. Similarly, the Te-doped samples exhibited notable increase in their band gap values after annealing. For example, the optical band gap of the sample doped at x = 0.20 increased from 0.03 to 0.41 eV by annealing. On the other hand, transmittance was also enhanced by annealing. For samples treated at 250 °C for 3 h, their optical transmissivity is enhanced to over 99% at the visible near-IR range. Such significant enhancement can be ascribed to structural enhancements. With such enhancement in the optical transmissivity, optoelectronic applications including transparent electrode can be met.